National Infrastructure for University Repositories Possible Model - Kristina Varbanova-Dencheva; Radostina Todorova (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
Paper stresses on the active role of university repositories in sustaining a long-term strategy to increase impact and visibility of Bulgarian research. Authors would like to draw the attention of a critical disadvantage of the research exchange progress in Bulgaria and suggest continuing the development of good practices, in establishing a national information infrastructure, based on an already functioning integrated platform. A short description of Primo Discovery and Delivery solution potential is discussed to show the variety of functional and technological solutions that it can add to a national-wide research exchange network. A brief overview is made of the first institutional repositories, incorporated in Primo and the positive outcomes of the integration.